A general method to fabricate MoO3/C composites and porous C for asymmetric solid-state supercapacitors. Issue 23 (30th April 2019) - Jiang, Yu; Yan, Xuemin; Cheng, Yapeng; Zhang, Yan; Xiao, Wei; Gan, Lu; Tang, Haolin
Abstract : The obtained MCs electrode exhibits remarkable electrochemical performance in both aqueous and all-solid systems (220.5 F g −1 at 0.5 A g −1 with porous C as the positive electrode), certifying its excellent potential in supercapacitors. Abstract : MoO3 is one of the most promising electrodes for high energy density supercapacitors due to its layered structure, which facilitates the insertion/removal of small ions. However, the commercial recognition of MoO3 -based electrodes has been hampered by their low electronic conductivity, poor structural stability and narrow working potential window. A MoO3 /C composite (MCs) has been synthesized by a polymerization method followed by calcination of the obtained hydrogel. The obtained MCs electrode exhibits remarkable electrochemical performance in both aqueous (432.5 F g −1 at a current density of 0.5 A g −1, 100% capacity retention after 10 000 cycles) and all-solid (220.5 F g −1 at 0.5 A g −1 ) systems with porous C as the positive electrode, demonstrating its potential in commercial utilization.